2008
DOI: 10.3399/bjgp08x341959
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency treated by consuming UVB-irradiated mushrooms

Abstract: Deficiency of vitamin D is usually caused by dietary deficiency and/or lack of exposure to sunlight in dark skinned individuals living at northern latitudes. Simple vitamin D deficiency is commonly treated by prescribing a vitamin D containing calcium supplement. This report presents a patient who rejected this approach and instead, after researching alternative treatment options independently, opted to self-treat by consuming UVB-irradiated mushrooms. The beneficial effect of this on the patient's plasma bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 10 publications
3
7
0
Order By: Relevance
“…Some studies suggested that stress factors indicate the elevated synthesis of carotenoids (Kim et al, 2012). Others show that polyphenol content increases during UV-stress to protect the plant tissues from damages (Ozzard et al, 2008). Similar results were obtained from measurements performed on fruits exposed to insect invasions (Felton et al, 1994;Hemingway & Laks, 1992).…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Some studies suggested that stress factors indicate the elevated synthesis of carotenoids (Kim et al, 2012). Others show that polyphenol content increases during UV-stress to protect the plant tissues from damages (Ozzard et al, 2008). Similar results were obtained from measurements performed on fruits exposed to insect invasions (Felton et al, 1994;Hemingway & Laks, 1992).…”
Section: Introductionsupporting
confidence: 75%
“…malignant tumours, non-alcoholic fat liver, autoimmune diseases etc.) (Felton et al, 1994;Geösel et al, 2011;Ozzard et al, 2008) can be developed by the damages in DNA and the structural and functional proteins evoked by these reactive substances (Bagchi et al, 2000). Because of this, many studies investigated how efficient the different foods are (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently the case history of a patient with vitamin D deficiency and secondary hyperparathyroidism was published, who refused to take supplements, but self-treated his deficiency by consuming mushrooms daily, which he had exposed to UV-B irradiation (Ozzard et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The role of innovation and technology in meeting individual nutritional needs 429S at UNIV OF CALIFORNIA SAN DIEGO on April 13, 2015 jn.nutrition.org added source of vitamin D (33), which is essential for bone health and is being investigated for cancer prevention and brain development (34). Fruit and vegetable edible films have also been produced to limit packaging waste, improve freshness, and enhance nutrient intake.…”
Section: Introductionmentioning
confidence: 99%